2019
DOI: 10.3389/fcimb.2019.00149
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the Lung Microbiome in Idiopathic Pulmonary Fibrosis Patients

Abstract: Lung microbiome ecosystem homeostasis in idiopathic pulmonary fibrosis (IPF) remains uncharacterized. The aims of this study were to identify unique microbial signatures of the lung microbiome and analyze microbial gene function in IPF patients. DNA isolated from BALF samples was obtained for high-throughput gene sequencing. Microbial metagenomic data were used for principal component analysis (PCA) and analyzed at different taxonomic levels. Shotgun metagenomic data were annotated using the KEGG database and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…A previous report showed that bacteria of the Staphylococcus and Streptococcus genera worsen the clinical outcome of IPF patients, suggesting their implication in the disease progression and pathogenesis 7 . Studies showing the relative abundance of Staphylococcus or Streptococcus genera in the fibrotic lung and its significant correlation with the host immune response in IPF patients further support the contribution of these bacteria genera in the pathogenesis of pulmonary fibrosis 6,42,[48][49][50][51][52] . However, the precise mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A previous report showed that bacteria of the Staphylococcus and Streptococcus genera worsen the clinical outcome of IPF patients, suggesting their implication in the disease progression and pathogenesis 7 . Studies showing the relative abundance of Staphylococcus or Streptococcus genera in the fibrotic lung and its significant correlation with the host immune response in IPF patients further support the contribution of these bacteria genera in the pathogenesis of pulmonary fibrosis 6,42,[48][49][50][51][52] . However, the precise mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…We found that, in addition to Staphylococcus nepalensis strain CNDG, sequences similar to corisin are highly conserved in several transglycosylases from other Staphylococcus species and some members of the microbial community that inhabit the normal or fibrotic lungs, including strains of Streptococcus pneumoniae and Mycobacterium abscessus 51,[58][59][60] . This observation suggests that a broad range of bacteria may be the source of corisin in pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…Several methods have been described in the literature to isolate bacterial DNA from BALF ( Supplementary Table 1 ; Charlson et al, 2011 ; Erb-Downward et al, 2011 ; Pragman et al, 2012 ; Willner et al, 2012 ; Borewicz et al, 2013 ; Han et al, 2014 ; Renwick et al, 2014 ; May et al, 2015 ; Bernasconi et al, 2016 ; Dickson et al, 2016a , b ; Laguna et al, 2016 ; Marsh et al, 2016 ; Wen et al, 2016 ; Frayman et al, 2017 ; Zemanick et al, 2017 ; Ahmed et al, 2018 ; Kloepfer et al, 2018 ; Pattaroni et al, 2018 ; Esther et al, 2019 ; Gomes et al, 2019 ; Jorth et al, 2019 ; Kyo et al, 2019 ; Schneeberger et al, 2019 ; Tong et al, 2019 ; Wang et al, 2019 ). In some instances, successful recovery of DNA has been associated with the utilization of large volumes of starting material.…”
Section: Resultsmentioning
confidence: 99%
“…Different DNA extraction techniques have been used to profile microbial communities from BALF samples; commercial silica column-based kits ( Charlson et al, 2011 ; Willner et al, 2012 ; Han et al, 2014 ; Renwick et al, 2014 ; May et al, 2015 ; Dickson et al, 2016b ; Laguna et al, 2016 ; Marsh et al, 2016 ; Wen et al, 2016 ; Zemanick et al, 2017 ; Ahmed et al, 2018 ; Pattaroni et al, 2018 ; Kyo et al, 2019 ; Schneeberger et al, 2019 ; Tong et al, 2019 ; Wang et al, 2019 ), magnetic beads-based procedures ( Erb-Downward et al, 2011 ; Pragman et al, 2012 ; Bernasconi et al, 2016 ; Frayman et al, 2017 ; Kloepfer et al, 2018 ; Esther et al, 2019 ; Gomes et al, 2019 ), homemade protocols ( Borewicz et al, 2013 ; Jorth et al, 2019 ), salt-extraction approaches or the use of cationic detergents in combination with the classical phenol-chloroform extraction technique ( Willner et al, 2012 ). However, not many studies have compared the efficiency of these protocols, particularly using samples from young children ( Willner et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the mere presence of a lung microbiome in IPF, the field has firmly established its correlative significance (figure 2): among patients with IPF, variation in lung microbiota correlates with variation in important aspects of the disease: disease status [11,12], alveolar inflammation [13,14], host genotype [11], and the systemic host response [15,16]. Further, several studies have independently established the prognostic significance of the lung microbiome in IPF: three separate analyses have demonstrated that variation in lung microbiota predict disease progression and mortality among patients with IPF [11,13,17].…”
mentioning
confidence: 99%